The Effect of Liquid Housing Wealth on College Enrollment - Lovenheim, Michael F. (Journal of Labor Economics, 2011)
This article uses short-run housing wealth changes to identify the effect of housing wealth on college attendance. I find that households used their housing wealth to finance postsecondary enrollment in the 2000s when housing wealth was most liquid; each $10,000 in home equity raises college enrollment by 0.7 of a percentage point on average. The effect is localized to lower-resource families, for whom a $10,000 increase in housing wealth increases enrollment by 5.7 percentage points. These estimates imply that the recent housing bust could significantly negatively affect college enrollment through reduction in the housing wealth of families with college-age children.